Effect of Floodplain Roughness on Velocity Distribution in Mountain Rivers. (2016) - Xing, Yun; Yang, Shengfa; Zhou, Huajun; Liang, Qiuhua
Abstract: This paper aims to investigate the velocity characteristics of compound rivers in mountain areas, featured with substantially different roughness between the main channel and floodplain. A series of flume experiments have been conducted to investigate the velocity distribution affected by different roughness in the main channel and its floodplain. The experimental data are analysed to obtain a new empirical formula to determine the velocity ratio between the main channel and the floodplain. In addition to the roughness, the ratio between the water depth in the main channel and the floodplain also affects the flow velocity. Therefore the velocity characteristics vary with the roughness and depth in the subsections of the compound channel. The new empirical formula is applied to estimate velocity in the upper reach of Yangtze River, in Chongqing, China. The calculated results are found to be consistent with the field measurements, demonstrating the potential of the formula for estimating velocity distribution in mountain rivers.